2008
DOI: 10.1158/1535-7163.mct-07-0475
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DNA binding of the NF-Y transcription factor by the pyrrolobenzodiazepine-polyamide conjugate GWL-78

Abstract: Many genes involved in cell cycle control have promoters that bind the heterotrimeric transcription factor NF-Y. Several minor-groove binding drugs have been shown to block interactions of transcription factors with cognate DNA-binding sequences. We showed previously that noncovalent minor-groove binding agents block interactions of NF-Y with the promoter of topoisomerase IIA (topo IIA). In this study, we investigated the ability of GWL-78, a pyrrolobenzodiazepine-poly(N-methylpyrrole) conjugate, to inhibit th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 24 publications
1
61
0
1
Order By: Relevance
“…Previous studies of the in vitro interaction of the polyamides with the topo IIa promoter utilized numerous biophysical assays. Cellular permeation and promoter interaction were indirectly assumed by increased levels of topo IIa in confluent cells as assessed by immunoblotting, chromatin immunoprecipitation, and cellular sensitization to etoposide (Hochhauser et al, 2007;Le et al, 2006;Kotecha et al, 2008). In this study, the nuclear accumulation and DNA binding of the polyamide is directly verified by detecting the increased fluorescence output.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous studies of the in vitro interaction of the polyamides with the topo IIa promoter utilized numerous biophysical assays. Cellular permeation and promoter interaction were indirectly assumed by increased levels of topo IIa in confluent cells as assessed by immunoblotting, chromatin immunoprecipitation, and cellular sensitization to etoposide (Hochhauser et al, 2007;Le et al, 2006;Kotecha et al, 2008). In this study, the nuclear accumulation and DNA binding of the polyamide is directly verified by detecting the increased fluorescence output.…”
Section: Discussionmentioning
confidence: 83%
“…Our research groups have previously employed the topo IIa promoter as a model system for proof of principle of the ability of polyamides to modulate gene expression in cells (Tolner et al, 2001;Le et al, 2006;Wells et al, 2006;Hochhauser et al, 2007;Kotecha et al, 2008;Franks et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…factor) is a ubiquitous heterotrimeric transcription factor formed from NF-YA, B, and C subunits that is required for cell proliferation. [26][27][28][29][30][31] We recently found that NF-Y is induced during atherosclerosis and restenosis in rodent models and humans and promotes platelet-derived growth factor-BB-dependent cyclin B1 expression, vascular smooth muscle cell proliferation, and neointimal lesion development in a mouse femoral artery denudation model. 14 The results in the current study demonstrate that the restenosis-risk T allele of −957[T/C], but not the C allele, generates a CCAAT box at position −959/−955 relative to the CCNB1 transcription initiation site that supports specific binding of NF-Y and drives NF-YA-dependent transcription of luciferase reporter plasmids.…”
Section: The −957t −475c and +102g Restenosis-risk Alleles Increasementioning
confidence: 99%
“…B. Endonuclease BamH1, [21] RNA-Polymerase [3a, 22] und Ligase 1 [23] ) und spezifischen Transkriptionsfaktoren (z. B. Sp1, [24] NF-Y [25] und NF-kB) [25a, 26] als auch die Regulierung verschiedener Signalwege (z. B. p53-abhän-gige und -unabhängige apoptogene, [27] JNK/AP-1-, [8] VEGF- [28] und SDF1a-Signalwege).…”
Section: Introductionunclassified